Współdziałanie nauczycieli i rodziców w tworzeniu warunków sprzyjających osiąganiu przez dziecko samodzielności w przedszkolu - Kalita, Edyta (Nauczyciel wczesnej edukacji kreatorem środowiska edukacyjnego dziecka, 2016)
Self-reliance is a very important feature of the child, which determines his future success in a life. It is characterized by dynamic development of the child. Pre-school period is an extremely important element in achieving self-reliance by a child. The term self-reliance is understood differently. It stands out certain aspects of this phenomenon. The content of this article is focused on the presentation, how a kindergarten favors to achieve a self-reliance by a child understandings not only as a self-service, but also as a self-reliance in task situations, finding out on social contacts and ability to manage their own emotions. Beyond the role of pre-school environment also draws attention to the big impact of the family environment on child development. Parents and teachers are the most important for the child’s independent behavior patterns. This issue will thoughts, insights, experiences kindergarten teacher, in which the work is based on the method of Maria Montessori.